Schwann cell-enriched cultures from adult human peripheral nerve: A technique combining short enzymatic dissociation and treatment with cytosine arabinoside (Ara-C) (2002)
Attempts to design the nerve cellular prostheses have focused on the production of autologous Schwann cells expanded in vitro as the essential component in the regeneration process of injured peripheral nerves. To obtain human Schwann cells of high quality we tested a short enzymatic dissociation protocol that optimized cellular viability levels. We also assessed patterns of bromodeoxyuridine (BrdU) incorporation in both Schwann cells and fibroblasts in the presence or absence of the antimitotic Ara-C, an enrichment option for adult human Schwann cell cultures. The Ara-C treated cultures showed a significantly higher Schwann cell percentage (95%), compared with that obtained in the absence of Ara-C (70%), indicating that this antimitotic acts to eliminate fibroblasts in each one of the applied pulses (four pulses). However, we have observed that the use of this antimitotic during prolonged periods of time produced a cumulative effect causing Schwann cell cytotoxicity. Therefore, we consider that our enzymatic dissociation technique and the application of only two pulses of Ara-C to the cultures are enough to achieve enrichment of adult human Schwann cells in culture.